2008
DOI: 10.1103/physrevlett.100.105701
|View full text |Cite
|
Sign up to set email alerts
|

Predictions of Dynamic Behavior under Pressure for Two Scenarios to Explain Water Anomalies

Abstract: Using Monte Carlo simulations and mean field calculations for a cell model of water we find a dynamic crossover in the orientational correlation time from non-Arrhenius behavior at high temperatures to Arrhenius behavior at low temperatures. This dynamic crossover is independent of whether water at very low temperature is characterized by a ''liquid-liquid critical point'' or by the ''singularity-free'' scenario. We relate to fluctuations of hydrogen bond network and show that the crossover found for for both … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
167
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 88 publications
(182 citation statements)
references
References 23 publications
14
167
1
Order By: Relevance
“…The theory reproduces volumetric properties such as the temperature of maximum density, the isothermal compressibility, the thermal expansion coefficient, and water's heat capacity in good agreement with the underlying MB model, which was previously studied by NPT Monte Carlo simulations, and in qualitative agreement with experimental trends. We find that applying pressure to water should reduce waters heat capacity which is consistent with works of Rebelo et al 84 and Kumar et al 85 Pressure also causes a negative thermal expansion coefficient at low temperature which is in agreement with experiments ͑below 4 C͒; see, for example, Ref. 86.…”
Section: Discussionsupporting
confidence: 80%
“…The theory reproduces volumetric properties such as the temperature of maximum density, the isothermal compressibility, the thermal expansion coefficient, and water's heat capacity in good agreement with the underlying MB model, which was previously studied by NPT Monte Carlo simulations, and in qualitative agreement with experimental trends. We find that applying pressure to water should reduce waters heat capacity which is consistent with works of Rebelo et al 84 and Kumar et al 85 Pressure also causes a negative thermal expansion coefficient at low temperature which is in agreement with experiments ͑below 4 C͒; see, for example, Ref. 86.…”
Section: Discussionsupporting
confidence: 80%
“…Dry ice CO2 becomes quartz-like and exhibits a rich phase diagram [437][438][439][440][441][442] [443] and pressure-induced amorphization [444,445]. With different arrangements of hydrogen bonding, H2O alone has fifteen stable phases and an additional fifteen distinctive metastable crystalline, amorphous, and fluid phases [97,267,394,396,[446][447][448][449][450][451][452][453][454][455][456][457][458][459]. Intermolecular interactions dictate the rich HP polymorphism [460] of solid oxygen.…”
Section: Phase Transitionsmentioning
confidence: 99%
“…In order to address this question, a number of models which display criticality were investigated as to the presence of fragile-to-strong transitions. [14][15][16] These studies have shown that on crossing the critical line, fragile-to-strong, strong-to-strong, or even fragile-to-fragile transitions could be observed, depending on the specific structure of the phases separated by the critical line. In the particular case of the associated lattice gas model ͑ALG͒, which presents two critical lines, two kinds of dynamic transitions are also present.…”
Section: Introductionmentioning
confidence: 99%